Desarrollo e implementación de una aplicación móvil que permita realizar el libro de obras de actividades de construcción ejecutadas por el VIVEM-EP. - González Pineda, Luis Alberto (2016)
The use of information and communication technologies in the companies and institutions, allow for automation of processes that are manually very tedious, this provides the user with information entry, is for this reason that the present work provides a solution to the complexity of manual processes. This project of thesis describes the development and implementation of the application to make the book of works of mobile construction activities in the Municipal utility of housing of Loja VIVEM-EP, thus improving data collection processes for work book, using new information and communication technologies, so that has been considered to implement a system that allows: enter the work book data from a mobile device, save these data on a web server, generate statistics reports and completion. For the fulfilment of the objectives for this project, we used techniques for collecting information such as: the interview and observation. Methods was used to the process and analysis of the information: deductive, inductive, and scientific. The application called "Libro de Obra VIVEM-EP" consists of two parts, on the one hand is the server that is responsible for managing users, manage construction projects, save all the information about the books of work and generate reports with this information, among others, this has been used free tools like programming languages PHP, HTML5, CSS3, Javascript , AJAX, an Apache web server, a MySQL database manager; While in the part of the mobile Java and the Android SDK as programming languages for the obtaining of data of the work book of activities of construction were used. The system has been developed according to the methodology ICONIX for being a process simplified compared to other processes, since it clearly presents the activities of each stage and displays a sequence of steps that must be followed.